EFEKTIVITAS APLIKASI JAMINAN KESEHATAN NASIONAL (JKN) Mobile DALAM MENINGKATKAN PELAYANAN PUBLIK DI RUMAH SAKIT UMUM DAERAH PROF. DR. H. ALOEI SABOE KOTA GORONTALO - Jashinda Liskarina Kadir; Nuzlan Botutihe; Rifka S. Akibu; Robin Pakudu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study, titled “The Effectiveness of the National Health Insurance (JKN) Mobile Application in Improving Public Services at RSUD Prof. Dr. H. Aloei Saboe, Gorontalo City,” aims to analyze the effectiveness of the JKN Mobile application in enhancing public service quality in the healthcare sector. The research uses a descriptive qualitative approach with data collection methods including observation, interviews, and documentation. The findings show that the implementation of the JKN Mobile application has been effective and has positively contributed to improving public services, particularly in terms of easier access to services, time efficiency, and greater transparency in healthcare delivery. The application also reflects the principles of public service oriented toward citizens in line with the New Public Service perspective. Although there are challenges such as differences in digital literacy among users and occasional technical issues, these do not significantly reduce the overall effectiveness of the service. Instead, they are considered part of the ongoing process of improving the digital system. Overall, the JKN Mobile application has strong potential to be further developed with continuous support from the hospital and BPJS Kesehatan to ensure more optimal and sustainable healthcare services.